Daily Journal Writing to Enhance Students’ Writing Skills - Sihite, Ester Eveline; Simanjuntak, Debora Chaterin (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2016)
This study aims to enhance students’ writing skills through Daily Journal writing. This research was divided into three steps: giving pre-test, giving treatment (writing daily journal), and giving posttest. The result showed significant difference between control and experimental group. Experimental participants was improved through the writing of daily journal, and the score gained by participants showed that there was a significant effect on students’ writing skills. The achievements showed that the mean difference of post-test scores between the two groups was -.45433 and for the standard error mean>was .03840 with pValue .050 (see Table 3), means that Ha is accepted and Ho is not accepted. It means, writing daily journal is strong enough to improve the students’ writing skills. Keywords: Journal Writing, Writing Skills, Daily Journal Variations